Development of hedonic price model of ghee - Sivaram, Muniandy (Indian Journal of Dairy Science, 2017)
A hedonic price model of ghee for India was developed estimating the implicit economic values associated with the characteristics of ghee such as brand, packaging material used, season and annual trend. The data for the study were collected from Indian Dairyman and the Karnataka Co-operative Milk Producers Federation Limited, Bengaluru, Karnataka State, India.Â  The hedonic model developed explained about 98% of variation in the prices of ghee.Â  The model suggested that along with the quality of ghee, building up the brand image and innovations in packaging will help enhancing value addition and the customer base. Such hedonic price analysis will help developing quality adjusted dairy price index for accurate monitoring of prices of dairy products.Â